Sistem Informasi Administrasi Pelayanan Narapidana pada Lapas Klas IIA di Kota Pontianak - Haykal, Mochamad; Priyanto, Heri; Nasution, Helfi (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2017)
Detainees Services Administration Information System at KLAS II prisons Pontianak City" created by researching that conducted in prisons KLAS IIA. The objective of this report is to analyze and make a better detainees administration system at Pontianak City prison that still using manual system until now. The new system designed is better than administration Detainees and Prisoners on PONTIANAK city that has not using a computerized system. The system is designed by SDLC modeling. The program platform is web application with MySQL database. The results from this thesis design is to make an Detainees Services Administration Information System. The test results show that the system can help the government in processing the detainees data and their families can get the information easily.